2018
DOI: 10.3389/fphys.2018.00674
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity Affects Muscle Regeneration After Murine Blunt Muscle Trauma—A Broad Spectrum Analysis

Abstract: Injury to skeletal muscle affects millions of people worldwide. The underlying regenerative process however, is a very complex mechanism, time-wise highly coordinated, and subdivided in an initial inflammatory, a regenerative and a remodeling phase. Muscle regeneration can be impaired by several factors, among them diet-induced obesity (DIO). In order to evaluate if obesity negatively affects healing processes after trauma, we utilized a blunt injury approach to damage the extensor iliotibialis anticus muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…It will be valuable for future studies to decipher the relative importance of specific dietary components, overall caloric content and fat mass of the individual prior to the ischaemic insult, in establishing the efficacy of post‐ischemic vascular remodelling and muscle regeneration. It is also important to note that a substantially greater degree of inflammation in ischaemic muscle injury has been reported by studies employing longer periods of HF diet feeding and in aged mice . Thus, it is probable that the initial physiological adaptations that enable skeletal muscle to cope with excess fatty acids can eventually be overwhelmed, resulting in accumulation of intramuscular triglycerides and development of inflammation and fibrosis, and this transition is likely influenced by age, genetics, diet composition and duration.…”
Section: Discussionmentioning
confidence: 99%
“…It will be valuable for future studies to decipher the relative importance of specific dietary components, overall caloric content and fat mass of the individual prior to the ischaemic insult, in establishing the efficacy of post‐ischemic vascular remodelling and muscle regeneration. It is also important to note that a substantially greater degree of inflammation in ischaemic muscle injury has been reported by studies employing longer periods of HF diet feeding and in aged mice . Thus, it is probable that the initial physiological adaptations that enable skeletal muscle to cope with excess fatty acids can eventually be overwhelmed, resulting in accumulation of intramuscular triglycerides and development of inflammation and fibrosis, and this transition is likely influenced by age, genetics, diet composition and duration.…”
Section: Discussionmentioning
confidence: 99%
“…49 Limited data suggest that skeletal muscle ectopic lipid infiltration impairs satellite cell activation, leading to a decrease of skeletal muscle regeneration potential. 7,27 We observed a significant reduction in cultured satellite cell numbers in WT HF diet mice. Moreover, we showed that obesity impairs satellite cell activation during early proliferation (ie 24 hours).…”
Section: Discussionmentioning
confidence: 75%
“…Satellite cells, the myogenic precursor stem cell population of the skeletal muscle, are of pivotal importance for skeletal muscle homeostasis and regeneration . Sparse evidence suggests that skeletal muscle regeneration is severely impaired in obese individuals possibly because of increased lipid deposition and perturbed satellite cell function . The fatty acid transporter CD36 plays an important role in skeletal muscle fatty acid transport and utilization .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 μm thick tissue-sections were deparaffinized, rehydrated in decreasing alcohol series and subsequently stained in hematoxylin for three minutes. Afterwards the sections were blued using running water for 10 min and subsequently stained in eosin for 10 s [32]. The staining was completed by implementing dehydration of the slides in increasing alcohol series with incubation in Roti®-Histol.…”
Section: Hematoxylin and Eosin (He) Stainingmentioning
confidence: 99%